Rancang Bangun Sistem Informasi Kegiatan Mahasiswa Berbasis Web Menggunakan Metode Agile di URI Academy - Haykal Azizi; Faiz Rizqi Hanafi; Jupron Jupron (IKRA-ITH Informatika : Jurnal Komputer dan Informatika, 2026)
URI Academy integrates various student development programs covering education, research, incubation, and networking with the industry. Challenges arise because the publication of research achievements and the dissemination of activity schedules still rely on manual methods. As a result, the delivery of information to students and industry partners is less than optimal. To address these issues, this study aims to design a web-based student activity information system at URI Academy using the agile methodology. The data collection process in this research combines interview techniques, direct observation, and literature review analysis. In terms of technology implementation, the system architecture uses the PHP programming language with MySQL as the database management system. The development of this system provides several key features, including an administrator dashboard, an activity release module, user data management, and an activity information center. Test results show that this platform offers easy accessibility for users. The system implementation has proven to enable more systematic and efficient student data management. The existence of this new system transforms the documentation process while optimizing the effectiveness of information distribution within the URI Academy environment.